Soczewki kontaktowe systematycznej wymiany w ocenie pacjentów - Orzałkiewicz, Alicja; Czajkowski, Grzegorz; Kałużny, Jakub (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
Purpose: To measure the level of satisfaction connected with use of frequent replacement contact lenses. Material and methods: Questionnaire forms were sent to 600 patients aged 7 to 54 years fitted with contact lenses between the years 1996 to 1999. Each questionnaire consisted of 31 questions about satisfaction, complications and every day care. Results: 281 patients ( 46,8% ) answered questionnaires, 94,7% of them were satisfied with the vision ensured by contact lenses. However 43 % of contact lenses wearers used one pair of lenses at last 1 week longer then it was allowed. Only 38% of them followed control visit schedule. Conclusions: Our study demonstrated high level of satisfaction related to the use of frequent repalcement contact lenses. However it was observed, that ophthalmologist indications were not completly fullfilled.